On-Surface Synthesis of Organolanthanide Sandwich Complexes - Mathialagan, Shanmugasibi K; Parreiras, Sofia O; Tenorio, Maria; Černa, Lenka; Moreno, Daniel; Muñiz-Cano, Beatriz; Navío, Cristina; Valvidares, Manuel; Valbuena, Miguel A; Urgel, José I; Gargiani, Pierluigi; Miranda, Rodolfo; et al. (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2024)
The synthesis of lanthanide-based organometallic sandwich compounds is very appealing regarding their potential for single-molecule magnetism. Here, it is exploited by on-surface synthesis to design unprecedented lanthanide-directed organometallic sandwich complexes on Au(111). The reported compounds consist of Dy or Er atoms sandwiched between partially deprotonated hexahydroxybenzene molecules, thus introducing a distinct family of homoleptic organometallic sandwiches based on six-membered ring ligands. Their structural, electronic, and magnetic properties are investigated by scanning tunneling microscopy and spectroscopy, X-ray absorption spectroscopy, X-ray linear and circular magnetic dichroism, and X-ray photoelectron spectroscopy, complemented by density functional theory-based calculations. Both lanthanide complexes self-assemble in close-packed islands featuring a hexagonal lattice. It is unveiled that, despite exhibiting analogous self-assembly, the erbium-based species is magnetically isotropic, whereas the dysprosium-based compound features an in-plane magnetization.
Keywords: STM/STS; XMCD; lanthanides; on‐surface synthesis; organometallic chemistry; density functional theory